2014
DOI: 10.1038/srep06426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recombinant Globular Adiponectin on Early Warm Ischemia-Reperfusion Injury in Rat Bile Duct after Liver Transplantation

Abstract: Adiponectin (APN) is an adipocyte protein with anti-diabetic properties, which has been recently revealed to have anti-inflammatory activity in organ ischemia- reperfusion injury (IRI). However, little is known about its function in bile duct IRI after liver transplantation. Therefore, we investigated whether APN affects early warm IRI in rat bile duct using a liver autologous transplantation model. In our study, rats were randomly divided into three experimental groups: a sham group, a IRI group, and a APN gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In our study, the decreased-donor graft recipients who had prolonged cold ischemia time and the living-donor graft recipients who had longer warm ischemia time, were found to have significantly higher incidences of newly onset proteinuria on the first day after operation. These findings are consistent with previous studies [ 39 43 ]. Moreover, the prevalence of proteinuria decreased significantly within 7 days after operation in the in-hospital and 90-day survival groups but not in the mortality groups (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the decreased-donor graft recipients who had prolonged cold ischemia time and the living-donor graft recipients who had longer warm ischemia time, were found to have significantly higher incidences of newly onset proteinuria on the first day after operation. These findings are consistent with previous studies [ 39 43 ]. Moreover, the prevalence of proteinuria decreased significantly within 7 days after operation in the in-hospital and 90-day survival groups but not in the mortality groups (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…However, pretreatment with TFs considerably reversed the alternations of these enzyme activities. The richest protein in neutrophils-MPO can be used as a quantitative measure of neutrophil infiltration [ 7 ]. Our results proved that TFs notably decreased neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Many basic and clinical experiments have demonstrated that hepatic I/R can induce direct cellular insult and delayed dysfunction, as well as the injury resulting from activating multiple oxidative stress and inflammatory pathways [ 5 , 6 , 7 ]. Sirtuin 1 (Sirt1) is a nicotinamide adenine dinucleotide (NAD + )-dependent nuclear class III histone deacetylase that participates in theregulation of metabolic and oxidative stress [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of adiponectin were found in BDL rats [284], reflecting the antifibrotic role of adiponectin, as adiponectin overexpression in activated HSCs was found to reduce the proliferation but augment the apoptosis of HSCs [280]. Consistent with this finding, adiponectin protected the rat bile duct against early warm ischemia-reperfusion injury by suppressing the inflammatory response and hepatocyte apoptosis and NF-κB (p65) played an important role in this process [285].…”
Section: Adiponectinmentioning
confidence: 67%